Involvement of membrane-bound viral glycoproteins in adhesion of pseudorabies virus-infected cells. - Hanssens, F P (1993)
Cell-associated spread of pseudorabies virus (PrV) plays an important role in the pathogenesis of the disease. Besides the already known direct cell-to-cell spread of the virus in monolayers, adhesion and subsequent fusion of suspended PrV infected cells to monolayers of uninfected cells are thought to occur. To study the adhesion of PrV-infected cells, an in vitro model was developed in SK-6 cells. Specific adhesion of PrV-infected cells to an uninfected monolayer started 5 h after infection of the cells and reached a maximum 6 h later. A correlation was found between the surface expression of PrV glycoproteins on the infected cells and the adhesion of these cells. PrV hyperimmune serum completely inhibited binding of the infected cells. To investigate which PrV envelope glycoproteins were responsible for the cell adhesion, the infected cells were incubated with antisera against glycoproteins gII, gIII, and gp50. Antiserum against either gII or gIII inhibited cell adhesion, and antisera against gII and gIII together had a cooperative effect. Antiserum against gp50 had no effect on binding when used alone but enhanced the inhibition induced by gII and gIII antisera. Heparin and neomycin inhibited adhesion, showing that the receptor for adhesion was a heparinlike substance. SK-6 cells infected with a gIII deletion mutant of PrV exhibited a much lower adhesion. This binding was heparin and neomycin independent and was not blocked by anti-gII serum. Nevertheless, it was completely inhibited with PrV hyperimmune serum and with anti-gp50 serum. This finding demonstrates that the ligand for adhesion of gIII(-)-infected cells is glycoprotein gp50. These results strongly suggest that the mechanism for adhesion of a PrV-infected cell to an uninfected monolayer is similar to the mechanism of adsorption and penetration of a PrV virion to a host cell.